How often do mosquitoes bite humans in southern England?: a standardised summer trial at four sites reveals spatial, temporal and site-related variation in biting rates - Brugman, Victor A.; England, Marion E.; Stoner, Joanne; Tugwell, Laura; Harrup, Lara E.; Wilson, Anthony J.; Medlock, Jolyon M.; Logan, James G.; Fooks, Anthony R.; Mertens, Peter P.C.; Johnson, Nicholas; Carpenter, Simon (BioMed Central, 2017)
Background